Autologous blood resuscitation for large animals in a research setting using the Hemafuse device: Preliminary data of device use for controlled and real-world hemorrhage - Treffalls, Rebecca N.; Lubas, Matthew; Morrison, Jonathan J.; Stonko, David P. (Frontiers in Veterinary Science, 2022)
Introduction New low-cost technologies are needed to salvage lost blood in low-resource settings and large animal laboratories. The Hemafuse device is a simple mechanical device that can recover lost blood during surgery. The aim of this study is to assess the feasibility of this device for resuscitating large animals with controlled and unintended hemorrhage and to provide device considerations for use in this context. Methods This study had two experimental components: (1) the Hemafuse device was kept on-shelf and used as needed to assess real-world use for unintended hemorrhage during experiments, and (2) animals underwent a controlled hemorrhage protocol, where four anesthetized swine underwent aortic and external jugular vein catheterization for pressure monitoring. Animals were hemorrhaged into the pelvis, and the Hemafuse device was used to suction the blood through a filter and pushed into a heparinized bag for subsequent retransfusion. Blood samples were collected at baseline, hemorrhage, within the device, and post-retransfusion and laboratory tests were performed. Results Animals that underwent controlled hemorrhage had a baseline mean arterial pressure of 83.6 ± 7.8 mmHg, and central venous pressure of 12.8 ± 1.9 mmHg, with expected changes throughout hemorrhage and resuscitation. Following resuscitation, pH was similar to baseline (7.39 ± 0.05 vs. 7.31 ± 0.03, p = 0.24). Lactate increased throughout the experiment with no significant differences after autotransfusion compared to baseline (2.7 ± 0.7 vs. 4.1 ± 1.4 mmol/L, p = 0.37). There were no significant changes in metabolic physiology. Compared to baseline, the hemoglobin (7.8 ± 2.4 vs. 7.3 ± 1.8 g/dL, p = 0.74), hematocrit (23% ± 6.9 vs. 21.3% ± 5.6, p = 0.71), and activated clotting time (268.5 ± 44.5 vs. 193 ± 24.6 s, p = 0.35) were similar after retransfusion. When used for unintended hemorrhage, the animals were resuscitated using the device with a mean time to retransfusion time of 128.7 ± 13.3 s and 100% survival throughout the experiment. Conclusion The Hemafuse device is feasible and efficacious for supporting large animal resuscitation. This is preliminary evidence that the device is a low-risk and low-cost off-the-shelf option for resuscitation using autologous blood with no significant effect on physiology post-retransfusion. We recommend that research laboratories consider the Hemafuse device for emergency use, particularly for highly invasive surgical laboratories where banked blood is not readily available.